2014
DOI: 10.1007/s12033-014-9825-2
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Quality Controls on Leishmaniases Molecular Tests to Increase Diagnostic Accuracy in Research and Reference Laboratories

Abstract: Early detection of leishmaniases and prompt institution of treatment are paramount for individuals and communities affected by these diseases. To overcome the remaining limitations inherent to molecular methods currently used and to ensure the accuracy of results in leishmaniases diagnosis, two triplex polymerase chain reaction (PCR) assays with quality controls for the reactions were developed. Validity indicators were assessed in 186 dog blood samples from endemic areas in Brazil. The level of agreement betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The novel assay includes an exogenous control, which controls for extraction and PCR performance, and an external positive control, controlling for PCR performance. The inclusion of quality controls, both internal and external, was highlighted as important in Leishmania detection assays [13]. The turn-around time is less than 2.5 hours from sample to result, and the system has a small laboratory footprint (the area required in the laboratory for instrumentation) of 75cm by 75cm.…”
Section: Discussionmentioning
confidence: 99%
“…The novel assay includes an exogenous control, which controls for extraction and PCR performance, and an external positive control, controlling for PCR performance. The inclusion of quality controls, both internal and external, was highlighted as important in Leishmania detection assays [13]. The turn-around time is less than 2.5 hours from sample to result, and the system has a small laboratory footprint (the area required in the laboratory for instrumentation) of 75cm by 75cm.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced in Figure 2, the amplification of the parasite DNA is favored, and this is associated with the design of the probes, as well as with the chosen targets. The large amount of the host's genetic material that is simultaneously purified in the extraction step could impair the detection of the etiological agent DNA, mainly because of competition between the primer sets for the PCR reagents 9,25 . In larger parasite DNA concentrations, there is no amplification of the G3PD gene (as from the concentration of 2x10 3 fg per µL of sample), but this does not affect the validation of the results, since the intention of the reaction is to favor the target DNA appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Gonçalves et al 8 used the same sample quality control (G3PD gene) in multiplex reactions to detect VL through conventional PCR (cPCR) reactions, and demonstrated that it was possible to detect potential false negative results in 33% of the samples tested (no amplification of the G3PD gene). Gonçalves-de-Albuquerque et al 25 standardized multiplex cPCR reactions for the diagnosis of VL in dogs, also using the G3PD gene as a quality control, and more than 15% of the samples were considered unsuitable for diagnostic definition because of no quality control amplification in the negative samples. In this study, all samples with negative results in the duplex qPCR protocol presented amplification of the quality control.…”
Section: Discussionmentioning
confidence: 99%